The generic position of Rhinella skuki Caramaschi, 2012 (Anura, Bufonidae) - Caramaschi, Ulisses (Zootaxa, 2012)
The beaked toad Rhinella skuki was described by Caramaschi (2012) based on a specimen from Itacaré (14o17’S, 38o60’W; 13 m a.s.l.), in the Atlantic Forest of southern State of Bahia, Brazil. The species was associated to Rhinella boulengeri Chaparro, Pramuk, Gluesekamp & Frost, 2007, from which it would be distinguished by the smaller size (SVL 26.2 mm in male of R. skuki; 39.2–46.4 mm in males of R. boulengeri), snout long, narrow, spatulate, with lateral borders parallel and rounded tip viewed from above, and long, strongly acute, in profile (snout short, wide, approximately truncate in dorsal view, and only acute in profile in R. boulengeri), head longer than wide (wider than long in R. boulengeri), and dorsal tubercles large, uniformly distributed (dorsal tubercles small, numerous, densely distributed in R. boulengeri).